Towards modernism; transition, treachery and theatricality in William Empson’s readings of Shakespeare - Rowland Cotterill (Polish Journal of English Studies, 2022)
Leading British modernist writers, seeking and constructing mythic models of literary history to authorise their double-acts of critical construction and creative rebellion, had difficulties with Shakespeare. Eliot notoriously valorised, above his plays, the epics of Virgil and Dante; Wyndham Lewis played off Shakespearean against Machiavellian nihilism; Joyce generated for him a mythical and Oedipal biography. In this context Empson’s treatment of Shakespearean poetic drama stands out – for brilliant ingenuity, theatrical awareness, and relative subsequent neglect. This paper shall address Empson’s responses to three Shakespearean cases of problematic transition. Concerning Hamlet; why does the protagonist return, from England, so changed? Is the change superficial or real? Does Hamlet’s soliloquy, before departure, clarify or confuse the issue? Concerning Falstaff; how do developments, or continuities, in the role illuminate the links and the gaps between the plays of Henry IV and Henry V? Concerning Cleopatra; how do images of fertility and of destruction, how do practices of patience and caprice, map on to her options and actions in face of death? For Empson, indeed, encounters with death focus, supremely, options for self-assertion – hence, for both critical distinctions and inclusive richness.